2007
DOI: 10.1063/1.2743816
|View full text |Cite
|
Sign up to set email alerts
|

Highly textured Bi2Te3-based materials for thermoelectric energy conversion

Abstract: This work is concerned with Bi2Te3-based compounds known as being highly effective materials for thermoelectric applications near room temperature. These compounds are characterized by a remarkable anisotropy linked to their R3¯m crystal structure. Two textured p-type Bi0.4Sb1.6Te3 samples were prepared using a powder metallurgy approach, with the c axis parallel to the pressing direction. One sample was undoped while the second was doped with Pb which acts as an acceptor. The electrical conductivity, Hall coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 17 publications
2
53
0
2
Order By: Relevance
“…This is due to the fact, that in transverse to crystallographic c axis, TE power factor (numerator in ZT expression) is considerably higher, than in parallel to this direction, mainly due to higher electrical conductivity values. For powder metallurgy synthesized Bi 2 Te 3 -based materials, it was shown that moderate powder grinding pressures, might retain some of the crystallographic anisotropy, due to the weaker van der Waals bonding of atoms located in adjacent layers along c-axis, compared to ionic/covalent bonding between atoms located in each of the layers [31]. In this example, higher ZT values in transverse to powder pressing direction are expected as in single crystals.…”
Section: Multi-phase Thermoelectric Materialsmentioning
confidence: 90%
“…This is due to the fact, that in transverse to crystallographic c axis, TE power factor (numerator in ZT expression) is considerably higher, than in parallel to this direction, mainly due to higher electrical conductivity values. For powder metallurgy synthesized Bi 2 Te 3 -based materials, it was shown that moderate powder grinding pressures, might retain some of the crystallographic anisotropy, due to the weaker van der Waals bonding of atoms located in adjacent layers along c-axis, compared to ionic/covalent bonding between atoms located in each of the layers [31]. In this example, higher ZT values in transverse to powder pressing direction are expected as in single crystals.…”
Section: Multi-phase Thermoelectric Materialsmentioning
confidence: 90%
“…Since the rhombohedral Bi 2 Te 3 based alloys have a quasi-layered crystal structure, it is important to determine whether all these hot pressed samples are textured or not. The Orientation Factor F, which was used to quantitatively investigate the degree of preferred orientation of (0 0 l)-planes from the XRD results, is defined by the following formulae [22]:…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that due to the difference in the hole to electron mobility ratio parallel and perpendicular to the c-axis, [14] the influence of the minority carriers on the Seebeck coefficient in a pseudo-isotropic sample is deprived in comparison to a highly textured sample along the conversion direction. [7] The thermal conductivity κ of the pseudo-isotropic sample was deduced from the thermal conductivities of a highly textured sample along κ || and perpendicular κ ⊥ to the c-axis [7] as described in Airapetiants and Bresler model, [15] ) (1)…”
Section: A Homogenous Samplesmentioning
confidence: 99%
“…[5, 6] One must keep in mind, however, that samples prepared by powder metallurgy might not be perfectly oriented, and consequently their figure of merit may be reduced. On the other hand, by providing a strong preferred orientation (texture) [7] or taking advantage of the Functionally Graded (FG) concept, [8,9], the figure of merit values may be improved significantly, reaching levels comparable to those of single crystals.…”
Section: Introductionmentioning
confidence: 99%